The Influence of Workload and Compensation on Job Satisfaction of Operational and Purchasing Employees at PT. Orderplizz Indonesia Maju Surabaya - Fansuri, Sufi Hamzah; Irbayuni, Sulastri (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The development of globalization challenges has brought companies into a free era that is increasingly competitive in achieving goals through the utilization of human resources in labor productivity through employee job satisfaction. This research aims to research and analyze the influence of workload and compensation on employee job satisfaction at PT Orderplizz Indonesia Maju. The sample in this study was 37 respondents using the Non-Probability Sampling method with saturated sampling techniques. The data analysis technique uses Structural Equation Model- Partial Least Square (SEM-PLS). The research results showed that workload had a significant negative effect on acceptable job satisfaction and compensation had a significant positive effect on acceptable job satisfaction.